David K. Jordan. Gods, Ghosts, and Ancestors. The Folk Religion of a Taiwanese Village, University of California Press; Berkeley, Los Ángeles y Londres, 1972, 197 pp. - Devalle, Susana B. C. (Estudios de Asia y África, 1972)
-